Counterpublic health and the design of drug services for methamphetamine consumers in Melbourne - Duff, Cameron; Moore, David (SAGE Publications Ltd, 2015)
This article is interested in how notions of the ‘public’ are conceived, marshalled and enacted in drug-treatment responses to methamphetamine use in Melbourne, Australia. After reviewing qualitative data collected among health-care providers and methamphetamine consumers, we draw on the work of Michael Warner to argue that services for methamphetamine consumers in Melbourne betray ongoing tensions between ‘public’ and ‘counterpublic’ constituencies. Our analysis indicates that these tensions manifest in two ways: in the management of ‘street business’ in the delivery of services and in negotiating the meaning of health and the terms of its restoration or promotion. Reflecting these tensions, while the design of services for methamphetamine consumers is largely modelled on public health principles, the everyday experience of these services may be more accurately characterised in terms of what Kane Race has called ‘counterpublic health’. Extending Race’s analysis, we conclude that more explicit focus on the idea of counterpublic health may help local services engage with methamphetamine consumers in new ways, providing grounds for novel outreach, harm-reduction and treatment strategies.